2022
DOI: 10.1007/s11661-022-06693-3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Fatigue-Cracking Behaviors of Low Alloy Steels in Seawater for Offshore Engineering Structures

Abstract: The fatigue crack growth (FCG) properties of offshore engineering structural steel DH36Z35 were studied in air and an artificial seawater environment. Results show that the FCG rate in seawater is up to 134.5 pct higher than in air. The test results of FCG rate in air and seawater at different frequencies show that FCG in seawater is accelerated compared with that in air at frequencies below 7 Hz. The lower the frequency, the more obvious the acceleration. It is found that the larger the seawater flow rate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Zhao et al 3 studied the corrosion fatigue crack initiation mechanism of X80 steel in the marine environment and showed that, in addition to the influence of stress concentration caused by corrosion pits, corrosion products attached to the metal surface will also promote the initiation of corrosion fatigue cracks. Liu et al 4 studied the FCP performance of offshore engineering structural steel DH36Z35 in air and artificial seawater environments. The results indicated that the FCP rate in seawater is 134.5% higher than that in air.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 3 studied the corrosion fatigue crack initiation mechanism of X80 steel in the marine environment and showed that, in addition to the influence of stress concentration caused by corrosion pits, corrosion products attached to the metal surface will also promote the initiation of corrosion fatigue cracks. Liu et al 4 studied the FCP performance of offshore engineering structural steel DH36Z35 in air and artificial seawater environments. The results indicated that the FCP rate in seawater is 134.5% higher than that in air.…”
Section: Introductionmentioning
confidence: 99%